Anatomical and radiological approach to pterygoid implants: a cross-sectional study of 202 cone beam computed tomography examinations. Issue 5 (May 2016) - Rodríguez, X.; Lucas-Taulé, E.; Elnayef, B.; Altuna, P.; Gargallo-Albiol, J.; Peñarrocha Diago, M.; Hernandez-Alfaro, F.
Abstract: The aim of this study was to define the three-dimensional angulation of the pterygomaxillary corridor in which pterygoid implants should ideally be placed. A secondary objective was to study the bone density in the tuberosity area and pterygoid plate. Two hundred and two cone beam computed tomography files of atrophic posterior maxillae were evaluated. Implant placement was guided by the individual anatomy of each patient. The mean implant angulation was 74.19 ± 3.13° in the anteroposterior axis and 81.09 ± 2.65° in the buccopalatal axis, relative to the Frankfort plane. Density in the tuberosity area ranged from 285.8 to 329.1 DV units and density in the pterygoid plate area from 602.9 to 661.2 DV units, with a 95% confidence interval. The density in the pterygoid area was 139.2% greater than in the tuberosity zone. Implant placement should be guided by the individual anatomy of each patient. Statistically significant differences were found between the tuberosity and pterygoid plate in terms of bone density. Based on the results of this study, an implant of at least 15 mm long should be used in order to take advantage of the quantity and quality of the bone in this region.